2005
DOI: 10.1111/j.1472-8206.2005.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy‐like reactions to iodinated contrast agents. A critical analysis

Abstract: Allergy-like reactions may occur following administration of iodinated contrast media (CM), mostly in at-risk patients (patients with history of previous reaction, history of allergy, co-treated with interleukin-2 or beta-blockers, etc.) but remain generally unpredictable. Severe and fatal reactions are very rare events. All categories of CM may induce such reactions, although first generation (high osmolar CM) have been found to induce a higher rate of adverse events than low osmolar CM. However, no differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(18 citation statements)
references
References 115 publications
(232 reference statements)
2
12
0
Order By: Relevance
“…Dahlstrom et al [28 ]reported the rate of adverse reactions to another nonionic monomer, iohexol, to be 0.8%. As nonionic CMs, iohexol, iomeprol and iopromide were the most common CMs in our study, and our current prevalence rate was comparable with the data reported by studies with nonionic CMs [4,6,7,8,9]. However, the past prevalence rate was relatively higher than current reactions to CMs during the 1-year study period (2.92 vs. 0.72%).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Dahlstrom et al [28 ]reported the rate of adverse reactions to another nonionic monomer, iohexol, to be 0.8%. As nonionic CMs, iohexol, iomeprol and iopromide were the most common CMs in our study, and our current prevalence rate was comparable with the data reported by studies with nonionic CMs [4,6,7,8,9]. However, the past prevalence rate was relatively higher than current reactions to CMs during the 1-year study period (2.92 vs. 0.72%).…”
Section: Discussionsupporting
confidence: 52%
“…The introduction of nonionic CMs has been associated with reduced adverse reactions to CM administration [4,6,7,8,9]. The overall rate of adverse reactions to iopromide, a nonionic monomer, was reported to be 1.5% in a large-scale surveillance study [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, as it has been earlier reported for immediate [16, 17] and delayed reactions from RCM [7, 8], premedication with corticosteroids and antihistamines is not always protective in delayed as well as immediate reactions from RCM.…”
Section: Discussionmentioning
confidence: 80%